Shining light on the dark sector: search for axion-like particles and other new physics in photonic final states with FASER - The FASER collaboration; Roshan Mammen Abraham; Xiaocong Ai; John Anders; Claire Antel; Akitaka Ariga; Tomoko Ariga; Jeremy Atkinson; Florian U. Bernlochner; Emma Bianchi; Tobias Boeckh; Jamie Boyd; et al. (Journal of High Energy Physics)
Abstract The first FASER search for a light, long-lived particle decaying into a pair of photons is reported. The search uses LHC proton-proton collision data at s $$ \sqrt{s} $$ = 13.6 TeV collected in 2022 and 2023, corresponding to an integrated luminosity of 57.7 fb −1. A model with axion-like particles (ALPs) dominantly coupled to weak gauge bosons is the primary target. Signal events are characterised by high-energy deposits in the electromagnetic calorimeter and no signal in the veto scintillators. One event is observed, compared to a background expectation of 0.44 ± 0.39 events, which is entirely dominated by neutrino interactions. World-leading constraints on ALPs are obtained for masses up to 300 MeV and couplings to the Standard Model W gauge boson, g aWW , around 10 −4 GeV −1, testing a previously unexplored region of parameter space. Other new particle models that lead to the same experimental signature, including ALPs coupled to gluons or photons, U(1) B gauge bosons, up-philic scalars, and a Type-I two-Higgs doublet model, are also considered for interpretation, and new constraints on previously viable parameter space are presented in this paper.